Literature Study on the Application of Reading and Writing Media in Elementary School Students in Developing Students' Cognitive Abilities Through the School Literacy Movement - Teofilus Ardian Hopeman (Eastasouth Institute, 2023)
In the 21st century, the School Literacy Movement (GLS) is being intensively held throughout Indonesia, facilitated by the Indonesian ministry of education. This is the government's effort to reduce Indonesia's actual illiteracy rate. GLS itself has several important parts in it that can support the implementation of these activities. Including reading and writing activities. Reading and writing activities can be integrated with media, making doing homework and writing more enjoyable. Some media that can improve students' cognitive abilities are cards, crossword puzzles, reading books, and story books. Through some of these media, it is hoped that it can facilitate students in developing their cognitive abilities in terms of writing and reading.